Research progress on NAT10-mediated acetylation in normal development and disease - Da Qin; Qing Liu; Xiaochao Ma; Rui Wang; Tianyu Lu; Yue Yang; Ze Tang; Yanbo Zhu (Frontiers in Cell and Developmental Biology)
N4-acetylcytidine (ac4C) is an evolutionarily conserved RNA modification catalyzed by the acetyltransferase NAT10. It regulates RNA stability, translation, and post-transcriptional processes. Meanwhile, NAT10 functions as a dual-function enzyme exhibiting both protein acetyltransferase and RNA acetylase activities. This review summarizes the structural and functional roles of NAT10-mediated acetylation in physiological contexts, including cell division, differentiation, inflammation, aging, and viral infection, as well as its emerging roles in cancer. In malignancies, NAT10-mediated acetylation drives tumor progression by enhancing mRNA stability, regulating cell cycle, promoting metastasis, suppressing ferroptosis, modulating metabolism, influencing p53 activity, mediating immune escape and fostering drug resistance. Interactions between NAT10 and non-coding RNAs further amplify its oncogenic effects. Unresolved questions, such as microbiota-mediated ac4C regulation and NAT10’s impact on the tumor immune microenvironment, highlight future research directions. Targeting NAT10 and ac4C modification presents promising therapeutic opportunities, with advanced technologies like single-cell sequencing poised to refine epitranscriptome-based interventions.